A Review On Immunomodulatory Effect Of Rasayana Therapy As A Prophylactic Measure In COVID-19 - Tripathi, Geetanjali; Singh, Archana (International Research Journal of Ayurveda & Yoga, 2020)
Coronavirus disease 2019 (COVID-19) is a newly emerged highly infectious disease that become the biggest health crisis for the world in this. The outbreak of the disease was initiated from the seafood market in Wuhan city of China in December 2019, and turned out to be a global health emergency. Due to its global quick spread and high fatality ratio, the World Health Organization declared the COVID-19 outbreak a pandemic in March 2020. Till date there is no vaccine or confirmed treatment has been discovered in the World, various research institutes all over the world are trying their best to invent vaccine for COVID-19. Thus far the management of this pandemic lies on its preventive aspect by reducing its infectivity through following some basic steps such as social, distancing, proper hand washing, sanitization, using masks etc, and by enhancing immunity. In Ayurveda the Rasayan therapy is highly recommended for immunomodulation and supposes to have effective role in the prophylaxis and management of COVID-19 infection. This review article is based on various classics of Ayurveda , contemporary medical science, researches etc, to enlighten the immunomodulatory effect of Rasayan therapy as a prophylactic strategy against COVID-19.